Nanotopography and oral bacterial adhesion on titanium surfaces: in vitro and in vivo studies - Humberto Osvaldo SCHWARTZ-FILHO; Tauane Ramaldes MARTINS; Paulo Roberto SANO; Marcela Takemoto ARAÚJO; Daniel Cheuk Hong CHAN; Nathália Ramaldes SALDANHA; Kátia de Pádua SILVA; Talita Signoreti GRAZIANO; William Cunha BRANDT; Caio Vinícius Roman TORRES; Karina COGO-MÜLLER (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The present study aimed to evaluate the influence of titanium surface nanotopography on the initial bacterial adhesion process by in vivo and in vitro study models. Titanium disks were produced and characterized according to their surface topography: machined (Ti-M), microtopography (Ti-Micro), and nanotopography (Ti-Nano). For the in vivo study, 18 subjects wore oral acrylic splints containing 2 disks from each group for 24 h (n = 36). After this period, the disks were removed from the splints and evaluated by microbial culture method, scanning electron microscopy (SEM), and qPCR for quantification of Streptococcus oralis, Actinomyces naeslundii, Fusobacterium nucleatum, as well as total bacteria. For the in vitro study, adhesion tests were performed with the species S. oralis and A. naeslundii for 24 h. Data were compared by ANOVA, with Tukey's post-test. Regarding the in vivo study, both the total aerobic and total anaerobic bacteria counts were similar among groups (p > 0.05). In qPCR, there was no difference among groups of bacteria adhered to the disks (p > 0.05), except for A. naeslundii, which was found in lower proportions in the Ti-Nano group (p < 0.05). In the SEM analysis, the groups had a similar bacterial distribution, with a predominance of cocci and few bacilli. In the in vitro study, there was no difference in the adhesion profile for S. oralis and A. naeslundii after 24 h of biofilm formation (p > 0.05). Thus, we conclude that micro- and nanotopography do not affect bacterial adhesion, considering an initial period of biofilm formation.